Post-protocol therapies in first-line immunotherapy trials in non–small cell lung cancer (NSCLC). Issue 28 (1st October 2022) - Desai, Aakash; Mansfield, Aaron Scott; Kommalapati, Anuhya; Leventakos, Konstantinos; Adjei, Alex A.; West, Howard Jack
Abstract : 125 Background: The advent of immunotherapy (IO) has led to significant improvement in outcomes for patients (pts) with advanced non-small cell lung cancer (adv NSCLC). The rate of crossovers and receipt of post-protocol IO in pivotal trials leading to FDA approvals of IO in NSCLC has not been systematically evaluated. Here, we evaluate crossover rates and post protocol therapies for pts with adv NSCLC across multiple first-line (1L) IO monotherapy and chemotherapy/IO (chemo/IO) combination trials. Methods: We utilized the publicly available data from pivotal clinical trials leading to approvals of IO or chemo/IO regimens in 1L treatment of adv NSCLC. We extracted data on outcomes, rate of crossover from control arm to IO, proportion of pts in control arm receiving IO and the start dates of these clinical trials. The primary outcomes were the rates of crossover and the proportion of patients in control arms who received post-control IO. Results: The study included 4 trials with IO monotherapy and 12 trials with chemo/IO combinations in 1L adv NSCLC. The primary endpoints for these trials were PFS (25%), OS (19%), and both PFS and OS (56%). The crossover rate from control arm to experimental arm (with IO) ranged from 0-74% in IO monotherapy trials and 0-49% in chemo/IO trials. Two IO monotherapy trials and five chemo/IO trials did not allow crossover; among them, 3 trials had a PFS/OS co-primary endpoint, while others had OS as primary endpoint. Ten of 16 trials provided explicit information on use of subsequent post-protocol therapies in their publications. Among the two IO monotherapy trials which did not allow crossover, post-protocol IO was administered in only 20-30% of patients. Among the six chemo/IO trials with information on post-protocol therapies, 30%-59% patients on the control arm subsequently received some form of IO on progression. Nine of 12 trials started accrual after 10/2015, when nivolumab was approved in the United States as second-line (2L) therapy for adv NSCLC regardless of tumor PD-L1 expression. Conclusions: Despite the highly significant OS benefit from 2L IO, which was the standard of care (SOC) in the United States, the rates of crossover and post-protocol IO administration was distressingly low in 1L IO monotherapy and chemo/IO trials for 1L adv NSCLC. This low rate of 2L treatment with IO may have been due to limited global availability prior to widespread regulatory approval during the conduct of these trials. There is an increased need for consistency in reporting of crossover treatment and post-protocol treatments to allow adequate assessment of the true 1L benefit with IO. Control arms in pivotal trials require scrutiny to ensure confirmation with SOC to provide access to optimal treatments for patients and prevent magnification of observed benefits in experimental arms. The difficulty lies in the global conduct of large randomized clinical trials with differing regulatory approvals.